Controlled size reduction of rare earth doped nanoparticles for optical quantum technologies. Issue 65 (5th November 2018) - Liu, Shuping; Serrano, Diana; Fossati, Alexandre; Tallaire, Alexandre; Ferrier, Alban; Goldner, Philippe
Abstract : Chemical etching is a promising way to synthesize RE:Y2 O3 nanoparticles with controlled size and long coherence lifetimes, opening the way to optical micro/nano-cavities coupling and efficient nanoscale quantum memories and processors. Abstract : Rare earth doped nanoparticles with sub-wavelength size can be coupled to optical micro- or nano-cavities to enable efficient single ion readout and control, a key requirement for quantum processors and high-fidelity single-ion quantum memories. However, producing small nanoparticles with good dispersion and exploitable optical coherence properties, another key aspect for these applications, is highly challenging by most synthesis and nano-fabrication methods. We report here on the wet chemical etching of Eu 3+ :Y2 O3 nanoparticles and demonstrate that a controlled size reduction down to 150 nm, well below the wavelength of interest, 580 nm, can be achieved. The etching mechanism is found to proceed by reaction with grain boundaries and isolated grains, based on obtained particles size, morphology and polycrystalline structure. Furthermore, this method allows maintaining long optical coherence lifetimes ( T 2 ): the 12.5 μs and 9.3 μs values obtained for 430 nm initial particles and 150 nm etched particles respectively, revealing a broadening of only 10 kHz after etching. These values are the longest T 2 values reported for any nanoparticles, opening the way to new rare-earth based nanoscale quantum technologies.